The Implications of Party Leadership Crises on Nigerian Democracy: A Comparative Analysis of the People’s Democratic Party (PDP) and All Progressives Congress (APC) - Usman Sambo; Abacha Umar Deribe; Babayo Sule; Umar Adamu; Ahmad Musa (RIRAI Publisher, 2022)
Political parties are the engine wheel and the machinery on which the vehicle of democracy thrives. Democracies require sound parties with focused leadership and a clear ideology for national development on the assumption of power. In Nigeria, the two dominant ruling parties of the People’s Democratic Party (PDP) which ruled for sixteen years and the All Progressives Congress (APC) which is currently in its fifth year of ruling are pre-occupied with internal leadership crises which collapsed the former and are threatening to tear the latter today. The inability of the country’s political leaders to establish parties with a dedicated and pragmatic party leadership is affecting the democratic governance in the country despite having the experience of the longest experiment in the history of the country. The research utilised both primary and secondary sources of data. The primary sources of data consist of an in-depth personal interview with some selected stakeholders in the subject matter of study and direct participant observation. The secondary sources are documented materials such as books, journals, internet sources and other related documents. A suitable framework; Game Theory was adopted to support the views presented in the work. The data obtained were discussed, analysed and interpreted using thematic content analysis and statistical modules. The work discovered that the leadership crises in the two dominant parties in Nigeria are affecting democratic delivery and good governance because of the power tussle. The work recommends among others that the parties must develop a culture of internal democracy and ideological focus with a frame for national interest and development.